Imaging Features of Renal Hydatid Cyst Presenting with Hydatiduria - Umar Amin; Khalid Siddique; Pervaiz Ahmad Aftab (Journal of Radiology Case Reports, 2009)
We report a case of renal hydatid cyst in a 25-year-old male who presented with hydatiduria. Intravenous pyelography revealed presence of a space-occupying lesion in the lower pole of right kidney with curvilinear calcifications. Ultrasound, computed tomography and MRI were suggestive of hydatid cyst in the right kidney. Patient underwent right-sided nephrectomy. Passage of hydatid cysts in urine is an exceedingly rare occurrence. Urinary tract involvement develops in 2-4% of all cases of hydatid cyst. Hydatiduria is an extremely rare manifestation of renal hydatid cyst. We report such a case with emphasis on IVU, sonographic, CT and MRI findings.